(untitled) (Zaporizhzhia Historical Review, 2021)
In the article the history of creation of hypothesis of “commanders of peacetime” of imperial direction of the post-Soviet historiography of Second World War has been considoreds, key positions of this hypothesis and the post-functional method closely associated with it have been set up and discovered.